Controllable and durable ionic electroactive polymer actuator based on nanoporous carbon nanotube film electrode. (19th July 2019) - Ru, Jie; Bian, Changsheng; Zhu, Zicai; Wang, Yanjie; Zhang, Junshi; Horiuchi, Tetsuya; Sugino, Takushi; Liu, Xiaofeng; Chen, Hualing; Asaka, Kinji
Abstract: Ionic electroactive polymer (iEAP) actuators have attracted great attention in the fields of micro-electromechanical systems and biomedicine due to their remarkably large strain under low-voltage stimulation. As actuation performance is mainly dominated by the electrochemical and electromechanical processes, the electrode layer and its structure are increasingly crucial to the actuators. In this research, we introduced a nanoporous carbon nanotube film with superior conductivity (1000–2000 S cm −1 ) as a cost-effective alternative electrode in fabricating iEAP actuators. The actuators were assembled by hot-pressing a Nafion/EMImBF4 electrolyte layer between two electrode films under vacuum conditions. Based on the developed porous hierarchal structure and superior electrical and mechanical properties of the electrode film, the actuators showed highly improved electrochemical and electromechanical properties and can operate controllably and durably under various voltage amplitudes and waveforms with a wide frequency range. The generated strain and stress reach up to 1.26% and 5.27 MPa, respectively, which are greater than the performances of the actuators based on polymer-supporting nano carbon electrodes. Once the voltage increases by 1 V, the strain and stress will increase by 0.336% and 1.407 MPa, respectively. The actuators can perform more than 20 000 cycles with an initial drop less than 20% in the operation stroke, showing a relatively durable and controllable cycle life. The newly developed actuators can be promising candidates for artificial muscles in academic interest and industrial applications.